Application of Convolutional Neural Network in the Segmentation and Classification of High-Resolution Remote Sensing Images (Global Journal of Computer Science and Technology, 2022)
Numerous convolution neural networks increase accuracy of classification for remote sensing scene images at the expense of the models space and time sophistication This causes the model to run slowly and prevents the realization of a trade-off among model accuracy and running time The loss of deep characteristics as the network gets deeper makes it impossible to retrieve the key aspects with a sample double branching structure which is bad for classifying remote sensing scene photos
Keywords: remote sensing; convolutional neural network; standard convolution; feature extraction